Подземные механизированные бункера - Мерцалов Р. В. Ростислав Владимирович; Солод Г. И. Григорий Иванович; Трухин П. М. Петр Михайлович; Син М. П. (Москва, Недра, 1985)
Авт. указаны на обороте тит. л.